Sociology 3212 -Race and Ethnic Relations - Gallagher, Charles (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course examines the sociology of racial, ethnic and cultural groups in the United States.Much of our focus will be on how these groups and inequality intersect. Why, for instance, are recent arrivals from certain parts of Asia (Laos and Cambodia) almost five times as likely as whites to live below the poverty line? Why are African Americans about three times as likely as whites to live below the poverty line? Just about every quality of life indicator (income, wealth, health, school attainment) points to inequities that are race based; yet America prides itself as being a nation which is "color blind."